2009
DOI: 10.1007/s10461-009-9646-7
|View full text |Cite
|
Sign up to set email alerts
|

HIV and Related Risk Behavior Among Men Who Have Sex with Men in Zanzibar, Tanzania: Results of a Behavioral Surveillance Survey

Abstract: We conducted a respondent driven sampling survey to estimate HIV prevalence and risk behavior among men who have sex with men (MSM) in Unguja, Zanzibar. Men aged ≥ 15 years living in Unguja and reporting anal sex with another man in the past 3 months were asked to complete a questionnaire and provide specimens for biologic testing. HIV prevalence was 12.3% (95% confidence interval 8.7, 16.3). HIV infection was associated with injecting drugs in the past 3 months, Hepatitis C virus infection and being paid for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
65
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 10 publications
9
65
2
Order By: Relevance
“…Meanwhile, these estimates are high compared to the prevalence rates in the overall male population in Brazil (HIV: 0.8%; syphilis: 1.3%) 4,20 , male industrial workers (HIV: 1.7%; syphilis: 1.9%) 21 , military conscripts (HIV: 0.1%; syphilis: 0.5%) 22 , and in the Bela Vista Project with MSM (HIV: 2.1%; syphilis: 13.5%) 23 . Recent studies that also used the RDS methodology among MSM in different countries showed HIV infection prevalence rates greater than 10% 6,24,25,26 , and some studies have shown prevalence rates greater than 30% 27,28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, these estimates are high compared to the prevalence rates in the overall male population in Brazil (HIV: 0.8%; syphilis: 1.3%) 4,20 , male industrial workers (HIV: 1.7%; syphilis: 1.9%) 21 , military conscripts (HIV: 0.1%; syphilis: 0.5%) 22 , and in the Bela Vista Project with MSM (HIV: 2.1%; syphilis: 13.5%) 23 . Recent studies that also used the RDS methodology among MSM in different countries showed HIV infection prevalence rates greater than 10% 6,24,25,26 , and some studies have shown prevalence rates greater than 30% 27,28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, whereas the national prevalence of HIV in Zambia was documented at 15.20% among heterosexual adults, it was 33.30% among MSM [56][57][58][59][60][61]. A similar trend was documented among Tanzanian MSM in Zanzibar, with 12.3% HIV prevalence while that of the local general population was 2.00% [9].…”
Section: Hiv Disparities and Syndemic Conditions Among Msm In Ssa: Pamentioning
confidence: 82%
“…Beyond this HIV disparity, the psychosocial problems such as depression, internalized homonegativity (IH) (Ross and Anderson, 2014), childhood sexual abuse (CSA), antigay violence (Anderson et al), and substance abuse were found to be prevalent and independently associated with HIV among MSM across countries in SSA [2,9,36,38,45]. Although syndemic theory has yet to be applied in the study of MSM in SSA, synthesis of the evidence has not only confirmed the existence of the HIV disparity but also strongly suggests the existence of a disproportionate level of multiple health problems that could plausibly affect the syndemic production of HIV among MSM.…”
Section: Hiv Disparities and Syndemic Conditions Among Msm In Ssa: Pamentioning
confidence: 99%
“…Mustanski et al and Klein later replicated these findings in an American sample of MSM and found that interactions among psychosocial health problems increased the odds of participation in condomless anal sex [13,26] in Tanzania also documented that higher numbers of MSM engage in receptive ("bottom") than in insertive anal sex; interpretation of this suggests the role played by gender in sexual positioning [15]. Dahoma et al also reported that more Tanzanian MSM engage in inconsistent condom use during receptive anal sex (90.8%) than they do during insertive anal sex (85.5%) [8]. The public health implication of this gendered sexual practice was substantively established by Beyrer et al who confirmed that the high probability of HIV transmission per act through the practice of receptive anal intercourse plays a central role in explaining the disproportionate disease burden in MSM [37].…”
Section: Hiv Risk-taking Behavior In African Cultural Contexts: Africmentioning
confidence: 95%
“…For example, despite the protective effect of the consistent use of condoms, condomless anal sex is still the greatest risk factor identified for HIV transmission among MSM [8]. However, the literature is full of empiric data confirming that a wide gap exists between the perception of HIV risks and the preventive measures practiced by MSM in countries in sub-Saharan Africa (SSA).…”
Section: Hiv Risk-taking Behavior In African Cultural Contexts: Africmentioning
confidence: 99%